Keberagaman Morfologi Dialek Bahasa Makassar di Kabupaten Bantaeng - Rahmi Mardatillah; Nurfadilah, Nurfadilah (Magister Pendidikan Bahasa dan Sastra Indonesia Universitas Jambi, 2025)
The purpose of this study is to explore morphological diversity in Makassar dialect in Bantaeng Regency. The method used is qualitative, with data collection through in-depth interviews and direct observation of native speakers. The focus of the research includes morphological variations such as the use of the prefix aN-, word repetition (reduplication), and word form changes. The results show that although there are dialectal differences between villages, the differences are not too great. This is influenced by the history and social interaction of the local community. Uniquely, some dialect characteristics persist despite the influence of Indonesian and other regional languages, showing the strength of local language and cultural identity. The benefits of this research are to enrich linguistic studies, especially on language diversity in South Sulawesi, and to support efforts to preserve local language and culture. In addition to being an academic document, this research is also expected to increase public awareness of the importance of keeping language heritage alive and passed on to the next generation. With this simplification, readers can more easily understand the objectives, methods, results, and benefits of the research without losing its importance.